(8aRS)-8,8a-Dihydrofuro[3,2-f]indolizine-6,9(4H,7H)-dione - Vrábel, Viktor (International Union of Crystallography, 2011)
The title compound, C(10)H(9)NO(3), is a chiral molecule with one stereogenic carbon atom, but which crystallizes as a racemate in the centrosymmetric space group P2(1)/n. The central six-membered ring of the indolizine moiety adopts a definite envelope conformation, while the conformation of the oxopyrrolidine ring is close to that of a flat-envelope with a maximum deviation of 0.352 (1) Å for the flap atom.